The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2002
DOI: 10.3758/bf03196298
|View full text |Cite
|
Sign up to set email alerts
|

Part-set cuing of false memories

Abstract: Part-set cuing inhibition describes the common finding that re-presenting items from a word list can reduce subjects' overall recall performance for studied items. Do part-set cuing effects occur for false memories as well? In the present experiments, subjects studied lists of words drawn from Roediger and McDermott (1995). After studying each list, subjects completed math problems and then recalled the list items either with or without accompanying list cues. In Experiment 1, the recall cues consisted of item… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 22 publications
5
31
0
Order By: Relevance
“…This finding extends the results from Experiment 1 for critical items' veridical recall to critical items' false recall. It is consistent with the results from very recent work, in which part-list cuing was also found to reduce false recall (Kimball & Bjork, 2002;Reysen & Nairne, 2002).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…This finding extends the results from Experiment 1 for critical items' veridical recall to critical items' false recall. It is consistent with the results from very recent work, in which part-list cuing was also found to reduce false recall (Kimball & Bjork, 2002;Reysen & Nairne, 2002).…”
Section: Discussionsupporting
confidence: 82%
“…We investigatedwhether part-list cuing and retrieval practice have the same or a different influence on critical items' false recall. In two very recent studies, how part-list cuing affects false recall has already been examined (Kimball & Bjork, 2002;Reysen & Nairne, 2002). In both studies, a number of DRM lists were presented to participants.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cuing and retrieval induced the same detrimental effects, on both "critical" items' veridical and "critical" items' false recall. Detrimental effects of partlist cuing on "critical" items' false recall have been reported in other recent studies as well (Kimball & Bjork, 2002;Reysen & Nairne, 2002; but see Marsh, McDermott, & Roediger, 2004). Also, previous studies have shown that retrieval of (Anderson et al, 1994) and cuing with 3 learned category exemplars impairs recall of a category's high-frequency, but not a category's lowfrequency, exemplars.…”
Section: Instructed Retrieval Inhibitionmentioning
confidence: 90%
“…This statement is still true today. Researchers remain interested in both the underlying mechanisms and such varied applications as part-set cuing effects in the false memory domain (e.g., Kimball & Bjork, 2002;Marsh, McDermott, & Roediger, 2004;Reysen & Nairne, 2002). In the current research program, we are interested in extending work on part-set cuing to older adults.…”
mentioning
confidence: 99%